Medical Brain Drain – Assessing the Role of Job Attributes and Individual Traits - Marco Bertoni; Debdeep Chattopadhyay; Yuanyuan Gu (Institute of Labor Economics (IZA), 2023)
We study physicians' migration intentions by undertaking a Discrete Choice Experiment with senior Italian medical students. Using the mixed logit models, we estimate how much income students are willing to forego for various job characteristics, including the job location. We find that future doctors are willing to sacrifice exteuro13,500/year on average to remain in their home country. Those with higher willingness to take risks, competitiveness, cognitive skills and altruism levels are more likely to migrate abroad, with implications for the quality of future doctors remaining in their home country. Furthermore, the valuations of several job characteristics differ substantially for jobs located in the home country or abroad, informing the design of job contracts that shall help retain young doctors.
Keywords: F66; I18; J08; 330; brain drain; medical workforce; job design; personality traits; discrete choice experiments